The Role of Teachers in Increasing Students' Health Awareness through the UKS Program at SDN 014 Samarinda - Sutiono, Ardi; Ediansyah, Ediansyah; Bobby, Andi; Warman, Warman; Fitriadi, Ahmad (Jurnal Riset Ilmu Pendidikan, 2025)
Health is an important factor in supporting the learning process of students in elementary schools. The School Health Program (UKS) aims to increase students' awareness of health through education and healthy living practices. This study analyzes the role of teachers in implementing the UKS program and the strategies used to increase students' health awareness at SDN 014 Samarinda Ulu. With a qualitative approach and case study method, data were collected through in-depth interviews, participatory observation, and documentation studies. The results of the study indicate that teachers act as educators, facilitators, and role models in forming students' healthy living habits. The strategies implemented include lectures, hygiene demonstrations, use of educational media, and integration of health into extracurricular activities. Evaluation is carried out through observation and project-based tests. Challenges in implementing the UKS program include limited health workers, inadequate facilities, and low participation of students and parents. Therefore, it is necessary to strengthen the UKS curriculum, increase teacher capacity, and collaborate with health institutions to ensure the program runs effectively and sustainably.